Body and transcendence in Virginia Woolf and Clarice Lispector = Corpo e transcendência em Virgínia Woolf e Clarice Lispector - Correia, Alda Maria (2013)
Virginia Woolf and Clarice Lispector belong to quite different historical, political and cultural contexts. Beyond its antecedents and roots in European modernism, Brazilian modernism developed according to peculiar patterns and lines, cultivating, for example, more clearly political, nationalist and regionalist tendencies than happened in the British area. Molly Hite’s essay “Virginia Woolf’s Two Bodies” suggests the existence of two kinds of body represented and perhaps experienced by Virginia Woolf: “one kind was the body for others, the body cast in social roles”, the other, the “visionary body”, a second physical presence, which brings into play new perspectives on the female modernist body and new strategies of political and aesthetic representation. It is this “visionary body”, that, in many moments, intersects with transcendence. These two kinds of body are also present in Clarice Lispector’s work, structured, of course, around other complexities and gradations, explained by a different temporal context, but still touching common seminal questions. In Lispector, it is through the body cast in social roles that you reach the “visionary body” and transcendence. The movement is not a flight, as in Woolf, on the contrary it is a necessity, a condition to get to the essence.